Self-assembled monomolecular layer organic semiconductor material based on indene [2, 1-b] carbazole as well as preparation method and application of self-assembled monomolecular layer organic semiconductor material

By developing a self-assembled single molecular layer organic semiconductor material based on, [2,1-B] and Kagazazo, it solves the problem of low relocation rate and high cost of existing cave transmission materials. Efficiency and low -cost production.

CN119371458APending Publication Date: 2025-01-28HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411288806.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The low mobility and high cost of hole transport materials in existing perovskite solar cells limit their large-scale applications.

Method used

Develop a self-assembly single-layer organic semiconductor material based on, [2,1-B] and Kagazazo. By regulating the peripheral modifier group, it optimizes the self-assembly and photoelectric performance of the material.

Benefits of technology

Realized low cost and good stability, as an indoor transmission layer to show high efficiency in the perovskite solar cell, short-circuit light current density reaches 25.96mA CM-2, the opening voltage is 1.18V, the filling factor is 0.7995, the optoelectronics is optoelectronics, and the optoelectronics The conversion efficiency reached 24.44 %.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371458A_ABST
    Figure CN119371458A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of perovskite solar cells, and particularly discloses a self-assembled monomolecular layer organic semiconductor material based on indene [2, 1-b] carbazole and a preparation method and application thereof.The indene [2, 1-b] carbazole and derivatives thereof are used as functional groups in semiconductor material molecules, and the semiconductor material molecules have a large conjugate plane structure, so that the structure of the semiconductor material is improved; according to the invention, phosphoric acid is taken as an anchoring group, strong intermolecular interaction is induced, molecules are promoted to form more ordered and compact SAM on an ITO substrate, two methyl groups on the SAM generate a spatial effect, aggregation and blockage at a crystal boundary in a film forming process are prevented, a recombination center is generated, and phosphoric acid is taken as the anchoring group, so that firm self-assembly of a self-assembly monomolecular layer on the surface of the ITO substrate can be realized. The self-assembled monomolecular layer organic semiconductor material has the advantages of good stability, expandability, no dopant, simple preparation and low cost. When the material is applied to a perovskite solar cell, the photoelectric conversion efficiency exceeding 24% can be obtained, and the material is an organic semiconductor material with a very good prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite solar cells and relates to the preparation of organic semiconductor materials, in particular to a self-assembled monolayer organic semiconductor material based on inden[2,1-b]carbazole and a preparation method and application thereof. Background Art

[0002] With the continuous development of science and technology, energy demand has become one of the urgent problems to be solved. The growing demand for energy and the depletion of traditional fossil energy have forced humans to explore a new type of sustainable energy to prepare for future energy depletion. Solar energy has the advantages of being renewable and pollution-free, inexhaustible, and unlike traditional fossil energy, which has a very long formation cycle. As one of the most common and considerable sustainable energy sources, it has gradually become a research hotspot for scientists in recent years.

[0003] How to utilize solar energy efficiently and at low cost has become the focus of people's attention. Perovskite solar cells have received widespread attention due to their simple preparation process, low cost and high efficiency. The hole transport layer plays an important role in extracting and transporting photogenerated holes generated by the perovskite layer and inhibiting electron backflow in perovskite solar cells. It is an important component of high-performance devices. Classic hole transport materials, such as 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-OMeTAD) and poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), have disadvantages such as low hole mobility and high price, which limit their large-scale application.

[0004] As hole transport materials, self-assembled monolayers (SAMs) have the characteristics of simple structure and flexible design. They can effectively adjust the interface energy level and reduce defect states based on molecular engineering. At the same time, this type of material also exhibits unique advantages such as small parasitic absorption, low material consumption, compatibility with stacked perovskite solar cells, and simplified large-area device manufacturing. It has become a popular choice for the preparation of high-efficiency perovskite solar cells. Therefore, the development of new SAM materials with simple structure, low cost and excellent performance is a key issue that needs to be solved to promote the industrialization of PSCs. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a self-assembled monolayer organic semiconductor material based on inden[2,1-b]carbazole, which is used as a hole transport layer, has low cost and good stability, and the SAMs molecule is scalable, has no dopants, is simple to handle and is cheap. The self-assembled monolayer organic semiconductor material of the present invention uses inden[2,1-b]carbazole as a functional group, butyl as a spatial connecting group, and phosphoric acid as an anchoring group. By regulating the peripheral modification groups, the self-assembly and photoelectric properties of this type of material can be further optimized.

[0006] The present invention is achieved through the following technical solutions:

[0007] A self-assembled monolayer organic semiconductor material based on inden[2,1-b]carbazole, the chemical structure of which is shown below:

[0008]

[0009] The substituent R is bromo, p-methoxyphenyl, p-fluorophenyl, 3,4,5-trifluorophenyl, pentafluorophenyl, 3,5-di(trifluoromethyl)phenyl, dibenzopyrrolyl, 4,4-dimethyldibenzopyridyl or 3,5-dicarboxylic acid methyl ester phenyl.

[0010] Specifically selected from the following structures:

[0011]

[0012] A further improvement of the present invention is:

[0013] A method for preparing a self-assembled monolayer organic semiconductor material based on indeno[2,1-b]carbazole comprises the following steps:

[0014] S1: Compound 1 undergoes a coupling reaction with a boronic acid or boronic acid lipid containing an R group to generate an intermediate 2;

[0015]

[0016] S2: Substitution reaction of intermediate 2 with dibromoalkane to generate intermediate 3;

[0017]

[0018] S3: causing intermediate 3 to undergo a substitution reaction with triethyl phosphite to generate intermediate 4;

[0019]

[0020] S4: hydrolyzing the intermediate 4 to generate the target product, i.e., the self-assembled monolayer material;

[0021]

[0022] The substituent R is bromo, p-methoxyphenyl, p-fluorophenyl, 3,4,5-trifluorophenyl, pentafluorophenyl, 3,5-di(trifluoromethyl)phenyl, dibenzopyrrolyl, 4,4-dimethyldibenzoacridinyl or 3,5-dicarboxylic acid methyl ester phenyl.

[0023] A further improvement of the present invention is:

[0024] In S1, under argon protection conditions, in toluene solvent, compound 1 is reacted with boric acid or boric ester containing a substituent R under the action of tetrakistriphenylphosphine palladium and potassium carbonate to generate compound 2, wherein the amount of the compound used is calculated by the amount of substance, compound 1: boric acid or boric ester containing a substituent R: tetrakistriphenylphosphine palladium: potassium carbonate = 1: 1-2: 0.02-0.1: 4-10, the reaction temperature is 90-110° C., and the reaction time is 6-12 h.

[0025] Furthermore, in S2, compound 2 is dissolved in DMF, and a substitution reaction occurs under the action of potassium hydroxide and tetrabutylammonium bromide (TBAB) to generate compound 3, wherein the amount of the compound is calculated based on the amount of substance, compound 2: dibromobutane = 1:5-20, the reaction temperature is 60-70°C, and the reaction time is 4-8h.

[0026] Further, in S3, in S3, compound 3 is reacted with triethyl phosphite under an argon atmosphere to generate compound 4, wherein the molar ratio of compound 3 to triethyl phosphite is 1:5-40, the reaction temperature is 100-200°C, and the reaction time is 10-20h.

[0027] Furthermore, in S4, compound 4 and bromotrimethylsilane are mixed in 1,4-dioxane, and a hydrolysis reaction is carried out under an argon atmosphere, and the reaction is carried out at 25 to 100° C. for 10 to 24 hours to obtain the target product ZF; the molar ratio of compound 4 to bromotrimethylsilane is 1:5 to 10.

[0028] A further improvement of the present invention is:

[0029] The above-mentioned self-assembled monolayer organic semiconductor material based on inden[2,1-b]carbazole is used as a hole transport layer in perovskite solar cells.

[0030] The beneficial effects of the present invention are:

[0031] 1. The self-assembled monolayer organic semiconductor material based on inden[2,1-b]carbazole provided by the present invention has a larger conjugated planar structure of the substrate indenylcarbazole and its derivatives, which induces stronger intermolecular interactions and promotes the molecules to form a more ordered and compact SAM on the ITO substrate. The two methyl groups on it produce a steric effect, preventing aggregation and clogging at the grain boundary during the film formation process, and generating a recombination center. At the same time, phosphoric acid as an anchoring group can realize the firm self-assembly of the hole transport material on the surface of the ITO substrate.

[0032] 2. The self-assembled monolayer organic semiconductor material provided by the present invention is used as a hole transport layer in perovskite solar cells. The test results show that the short-circuit photocurrent density of the battery device reaches 25.96 mA cm -2 , the open circuit voltage is 1.18V, the fill factor is 0.7995, and the photoelectric conversion efficiency reaches 24.44%, which has practical significance for improving the efficiency of perovskite solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The NMR spectrum of formula ZF1 prepared by the present invention;

[0034] Figure 2 The NMR spectrum of formula ZF2 prepared by the present invention;

[0035] Figure 3 The NMR spectrum of formula ZF3 prepared by the present invention;

[0036] Figure 4 The NMR spectrum of formula ZF7 prepared by the present invention;

[0037] Figure 5 Thermogravimetric analysis of formula ZF1 prepared by the present invention;

[0038] Figure 6 Thermogravimetric analysis of formula ZF2 prepared by the present invention;

[0039] Figure 7 Thermogravimetric analysis of formula ZF3 prepared by the present invention;

[0040] Figure 8 Thermogravimetric analysis of formula ZF7 prepared by the present invention;

[0041] Fig. 9 The JV curve of the perovskite solar cell prepared by using the formula ZF1 prepared by the present invention as the self-assembled monolayer hole transport material;

[0042] Fig.10 The JV curve of the perovskite solar cell prepared by using the formula ZF2 prepared by the present invention as the self-assembled monolayer hole transport material;

[0043] Fig.11 The JV curve of the perovskite solar cell prepared by using the formula ZF3 prepared by the present invention as the self-assembled monolayer hole transport material;

[0044] Fig.12 The JV curve of a perovskite solar cell prepared using the ZF7 prepared in the present invention as a self-assembled monolayer hole transport material. DETAILED DESCRIPTION

[0045] The present invention is described in detail below in conjunction with specific embodiments.

[0046] Example 1: Preparation of ZF1

[0047]

[0048] The synthetic route is as follows:

[0049]

[0050] (1) Synthesis of compound of formula 2:

[0051] Compound 1 (3.01 g, 6 mmol), p-methoxyphenylboronic acid (1.58 g, 7.5 mmol), tetrakistriphenylphosphine palladium (480 mg, 0.3 mmol), potassium carbonate (5 g) and water (5 mL) were added to a 100 mL single-mouth round-bottom flask in sequence, and the mixture was heated to 100 ° C and refluxed for 6-8 h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 5 / 1) to obtain 2.81 g of the compound shown in formula 2 as a white solid with a yield of 87%.

[0052] The structural characterization data of the compound of formula 2 are: 1 H NMR (400MHz, CDCl3): δ8.43(s,1H),8.31(s,1H),7.99(s,1H),7.85(d,J=7.4Hz,1H),7.68(d,J=8.7Hz,2H),7.61(dd,J=8.4,1.7H z,1H),7.46(d,J=7.4Hz,1H),7.40(dd,J=8.8,6.4Hz,3H),7.31(t,J=7.4Hz,1H),7.05(d,J=8.7Hz,2H),3.89(s,3H),1.55(s,6H).

[0053] (2) Synthesis of the compound of formula 3:

[0054] In a 100mL single-mouth round-bottom flask, raw material 2 (2.81g, 7.72mmol), 1,4-dibromobutane (16.67g, 77.2mmol), tetrabutylammonium bromide (322mg, 1mmol), potassium hydroxide (5.6g) and water (5.6mL) were added in sequence, and the mixed solution was heated to 70°C and refluxed for 6h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 3.21g of the compound shown in formula 3 as a white solid with a yield of 85%.

[0055] The structural characterization data of the compound of formula 3 are: 1 H NMR (400MHz, CDCl3): δ8.45(s,1H),8.32(d,J=1.5Hz,1H),7.84(d,J=7.4Hz,1H),7.71–7.62(m,3H),7.49–7.35(m,4H),7.30(t,J=7.4Hz, 1H),7.04(d,J=8.8Hz,2H),4.42(t,J=6.9Hz,2H),3.89(s,3H),3.44(t,J=6.4Hz,2H),2.20–2.06(m,2H),2.07–1.92(m,2H),1.60(s,6H).

[0056] (3) Synthesis of compound of formula 4:

[0057] Under argon protection, intermediate 3 (3.21 g, 5.51 mmol) and triethyl phosphite (20.34 g, 110.2 mmol) were added to a 100 mL two-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, the excess triethyl phosphite was distilled off under reduced pressure, and the crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 3.17 g of intermediate 4, a light yellow liquid, with a yield of 89%.

[0058] The structural characterization data of the compound of formula 4 are: 1H NMR (400MHz, CDCl3): δ8.40(s,1H),8.35(d,J=1.5Hz,1H),7.74(d,J=7.4Hz,1H) ,7.69–7.60(m,3H),7.47–7.30(m,4H),7.25(t,J=7.4Hz,1H),7.04(d,J=8.8Hz,2 H),4.56–4.43(m,2H),4.40(t,J=6.9Hz,2H),4.07–3.85(m,6H),3.89(s,3H),3. 46(dd,J=7.9,4.9Hz,2H),3.43(t,J=6.4Hz,2H),2.20–2.06(m,2H),1.60(s,6H).

[0059] (4) Synthesis of formula ZF1:

[0060] Under argon protection, intermediate 4 (3.17 g, 6.03 mmol), bromotrimethylsilane (8.34 g, 60.3 mmol) and 5 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 18 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was then recrystallized from ethanol and water to obtain 2.86 g of white ZF1 product with a yield of 85%.

[0061] The structural characterization data of the compound of formula ZF1 are: 1 H NMR (400MHz, DMSO) δ8.66(s,1H),8.45(s,1H),7.86(d,J=7.5Hz,1H),7.82(s,1H),7.73(d,J=8.7Hz,2H),7.69–7.63(m,2H),7.54(d,J=7.4Hz,1H ),7.36(t,J=7.4Hz,1H),7.26(t,J=7.3Hz,1H),7.07(d,J=8.8Hz,2H),4. 46(t,J=7.1Hz,2H),3.82(s,3H),2.00–1.80(m,2H),1.64–1.49(m,10H).

[0062] Example 2: Synthesis of ZF2

[0063]

[0064] The specific synthetic route is as follows:

[0065]

[0066] (1) Synthesis of the compound of formula 2:

[0067] In a 100mL single-mouth round-bottom flask, raw material 1 (3.01g, 6mmol), p-fluorophenylboric acid (1.83g, 9.5mmol), tetrakistriphenylphosphine palladium (346mg, 0.3mmol), potassium carbonate (5g) and water (5mL) were added in sequence, and the mixed solution was heated to 100°C and refluxed for 6-8h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 5 / 1) to obtain 2.73g of the compound shown in formula 2 as a white solid with a yield of 87%.

[0068] The structural characterization data of the compound of formula 2 are: 1 H NMR (400MHz, CDCl3): δ8.51 (s, 1H), δ8.44 (s, 1H), 8.33 (s, 1H), 7.89 (dd, J = 14.8, 7.6Hz, 1H) ,7.73–7.51(m,3H),7.69–7.21(m,4H),7.37–7.30(m,1H),7.21(ddd,J=8.7,4.4,2.2Hz,2H).

[0069] (2) Synthesis of the compound of formula 3:

[0070] In a 100mL single-mouth round-bottom flask, raw material 2 (2.73g, 7.23mmol), 1,4-dibromobutane (15.61g, 72.3mmol), tetrabutylammonium bromide (322mg, 1mmol), potassium hydroxide (5.6g) and water (5.6mL) were added in sequence, and the mixed solution was heated to 70°C and refluxed for 6h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 3.15g of the compound shown in formula 3 as a white solid with a yield of 85%.

[0071] The structural characterization data of the compound of formula 3 are: 1 H NMR (400MHz, CDCl3): δ8.48(s,1H),8.35(s,1H),7.89(dd,J=14.8,7.6Hz,1H),7.75–7.64(m,3H),7.53–7.38(m,4H),7.37–7.30(m ,1H),7.21(ddd,J=8.7,4.4,2.2Hz,2H),4.44(t,J=6.9Hz,2H),3.47(dd,J=7.9,4.9Hz,2H),2.29–1.92(m,4H),1.70–1.61(m,6H).

[0072] (3) Synthesis of compound of formula 4:

[0073] Under argon protection, intermediate 3 (3.15 g, 6.15 mmol) and triethyl phosphite (20.44 g, 123 mmol) were added to a 100 mL two-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, the excess triethyl phosphite was distilled off under reduced pressure, and the crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 3.12 g of intermediate 4, a light yellow liquid, with a yield of 89%.

[0074] The structural characterization data of the compound of formula 4 are: 1 H NMR (400MHz, CDCl3): δ8.66(s,2H),7.93–7.80(m,5H),7.73(d,J=8.6Hz,1H),7.55(t,J=5.9Hz,1H),7.37(d,J=7.4Hz,1H),7.28(t,J=7.3Hz ,1H),7.21(ddd,J=8.7,4.4,2.2Hz,2H),4.57–4.44(m,2H),4.09–3.79(m,6H),1.98–1.86(m,2H),1.61–1.49(m,8H),1.13(t,J=7.0Hz,6H).

[0075] (4) Synthesis of formula ZF2:

[0076] Under argon protection, intermediate 4 (3.12 g, 5.48 mmol), bromotrimethylsilane (8.39 g, 54.8 mmol) and 5 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 18 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was then recrystallized from ethanol and water to obtain 2.39 g of white ZF2 product with a yield of 85%.

[0077] The structural characterization data of the compound of formula ZF2 are: 1 H NMR (400 MHz, DMSO): 1H NMR(400MHz, DMSO)δ8.73–8.64(m,1H),8.53(d,J=14.9Hz,1H),7.89–7.78(m,4H),7.76–7.66(m,2H),7.55 (d,J=7.3Hz,1H),7.32(tt,J=14.6,7.5Hz,4H),4.59–4.40(m,2H),1.99–1.84(m,2H),1.68–1.52(m,10H).

[0078] Example 3: Synthesis of ZF3

[0079]

[0080] The specific synthetic route is as follows:

[0081]

[0082] 1) Synthesis of compound of formula 2:

[0083] In a 100mL single-mouth round-bottom flask, raw material 1 (3.01g, 6mmol), 3,4,5-trifluorophenylboric acid (1.8332g, 7.5mmol), tetrakistriphenylphosphine palladium (480mg, 0.3mmol), potassium carbonate (5g) and water (5mL) were added in sequence, and the mixed solution was heated to 100°C and refluxed for 6-8h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 5 / 1) to obtain 2.99g of the compound shown in formula 2 as a white solid with a yield of 87%.

[0084] The structural characterization data of the compound of formula 2 are: 1H NMR (400 MHz, CDCl3): δ8.66 (s, 1H), 8.45 (s, 1H), 7.86 (d, J = 7.5 Hz, 1H), 7.82 (s, 1H), 7.73 (d, J = 8.7 Hz, 2H), 7.69-7.63 (m, 2H), 7.54 (d, J = 7.4 Hz, 1H), 7.36 (t, J = 7.4 Hz, 1H), 7.26 (t, J = 7.3 Hz, 1H), 7.07 (d, J = 8.8 Hz, 2H), 4.46 (t, J = 7.1 Hz, 2H), 3.82 (s, 3H), 2.00-1.80 (m, 2H), 1.64-1.49 (m, 10H).

[0085] (2) Synthesis of the compound of formula 3:

[0086] In a 100mL single-mouth round-bottom flask, raw material 2 (2.99g, 7.2mmol), 1,4-dibromobutane (15.63g, 72.4mmol), tetrabutylammonium bromide (322mg, 1mmol), potassium hydroxide (5.6g) and water (5.6mL) were added in sequence, and the mixed solution was heated to 70°C and refluxed for 6h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 3.37g of the compound shown in formula 3 as a white solid with a yield of 85%.

[0087] The structural characterization data of the compound of formula 3 are: 1 H NMR (400MHz, DMSO) δ8.67(s,2H),7.85(dd,J=11.3,5.8Hz,5H),7.74(d,J=8.6Hz,1H),7.56(d,J=7.5Hz,1H),7.38(t,J=7.3Hz, 1H),7.28(t,J=7.5Hz,1H),4.54(t,J=6.4Hz,2H),3.61(t,J=6.4Hz,2H),2.00–1.87(m,4H),1.56(s,6H),1.24(d,J=4.2Hz,2H).

[0088] (3) Synthesis of compound of formula 4:

[0089] Under argon protection, intermediate 3 (3.37 g, 6.15 mmol) and triethyl phosphite (20.44 g, 123 mmol) were added to a 100 mL two-necked flask in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, the excess triethyl phosphite was distilled off under reduced pressure, and the crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 3.31 g of intermediate 4, a light yellow liquid, with a yield of 89%.

[0090] The structural characterization data of the compound of formula 4 are: 1 H NMR (400MHz, DMSO): δ8.66(s,2H),7.84(dd,J=17.4,9.5Hz,5H),7.73(d,J=8.6Hz,1H),7.56(d,J=7.4Hz,1H),7.38(t,J=7.4Hz,1H),7.28(t, J=7.3Hz,1H),4.51(t,J=6.8Hz,2H),3.94(dt,J=14.0,9.1Hz,6H),1.98–1.86(m,2H),1.55(s,7H),1.24–1.23(m,2H),1.13(t,J=7.0Hz,6H).

[0091] (4) Synthesis of formula ZF3:

[0092] Under argon protection, intermediate 4 (3.31 g, 5.47 mmol), bromotrimethylsilane (8.37 g, 54.7 mmol) and 5 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 18 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was then recrystallized from ethanol and water to obtain 2.55 g of white ZF3 product with a yield of 85%.

[0093] The structural characterization data of the synthesized ZF3 compound are: 1H NMR (400MHz, DMSO): δ8.65 (d, J = 2.4 Hz, 2H), 7.84 (dd, J = 9.8, 6.5 Hz, 5H), 7.71 (d, J = 8.6 Hz, 1H), 7.55 (d, J = 7.4 Hz, 1H), 7.37 (t, J = 7.2 Hz, 1H), 7.27 (t, J = 7.4 Hz, 1H), 4.48 (t, J = 6.8 Hz, 2H), 1.97–1.83 (m, 2H), 1.64–1.52 (m, 10H).

[0094] Example 4: Synthesis of ZF7

[0095]

[0096] The specific synthetic route is as follows:

[0097]

[0098] (1) Synthesis of the compound of formula 2:

[0099] In a 100mL single-mouth round-bottom flask, raw material 1 (3.01g, 6mmol), carbazole (1.74g, 7.5mmol), tetrakistriphenylphosphine palladium (346mg, 0.3mmol), potassium carbonate (5g) and water (5mL) were added in sequence, and the mixed solution was heated to 100°C and refluxed for 6-8h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 5 / 1) to obtain 3.24g of the compound shown in formula 2 as a white solid with a yield of 87%.

[0100] The structural characterization data of the compound of formula 2 are: 1H NMR (400MHz, CDCl3): δ8.45 (s, 1H), 8.32 (s, 1H), 8.10 (s, 2H), 8.08 (s, 2H), 7.82 (d, J = 7.4 Hz, 1H), 7.65 (d, J = 8.5 Hz, 1H), 7.44 (d, J = 0.8 Hz, 3H), 7.43 (s, 1H), 7.42 (s, 1H), 7.41 (s, 1H), 7.31 (d, J = 6.3 Hz, 1H), 7.25 (s, 1H), 7.23 (d, J = 2.8 Hz, 1H), 7.20 (d, J = 8.5 Hz, 1H), 1.55 (s, 6H).

[0101] (2) Synthesis of the compound of formula 3:

[0102] In a 100mL single-mouth round-bottom flask, raw material 2 (3.24g, 7.22mmol), 1,4-dibromobutane (15.59g, 72.2mmol), tetrabutylammonium bromide (322mg, 1mmol), potassium hydroxide (5.6g) and water (5.6mL) were added in sequence, and the mixed solution was heated to 70°C and refluxed for 6h. After the reaction solution was cooled to room temperature, dichloromethane and water were added for extraction, and the organic phase was distilled under reduced pressure. The crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 50 / 1 to 10 / 1) to obtain 3.58g of the compound shown in formula 3 as a white solid with a yield of 85%.

[0103] The structural characterization data of the compound of formula 3 are: 1 H NMR (400MHz, CDCl3): δ8.49(d,J=1.5Hz,1H),8.37(s,1H),8.15(s,1H),8.13(s,1H),7.85(d,J=7.5Hz,1H),7.72(d,J=8.5Hz,1H),7.49(s ,3H),7.45(s,2H),7.43(s,2H),7.29(s,1H),7.29(s,1H),7.28(s,2H),4.39(s,2H),3.41(s,2H),1.97(s,2H),1.95(s,2H),1.62(s,6H).

[0104] (3) Synthesis of compound of formula 4:

[0105] Under argon protection, intermediate 3 (3.58 g, 4.9 mmol) and triethyl phosphite (20.39 g, 98 mmol) were added to a 100 mL two-necked bottle in sequence. The reaction solution was heated to 165 ° C for 18 h. After the reaction solution was cooled to room temperature, the excess triethyl phosphite was distilled off under reduced pressure, and the crude product was subjected to column chromatography (eluent: petroleum ether / dichloromethane = 10 / 1 to 1 / 4) to obtain 3.50 g of intermediate 4, a light yellow liquid, with a yield of 89%.

[0106] The structural characterization data of the compound of formula 4 are as follows: 1H NMR (400 MHz, DMSO): δ8.56 (s, 1H), 8.15 (s, 2H), 8.13 (s, 2H), 7.63 (s, 2H), 7.61 (s, 2H), 7.46 (s, 1H), 7.44 (s, 2H), 7.42 (s, 1H), 7.20 (s, 1H), 7.19 (s, 2H), 7.17 (s, 1H), 3.88 (s, 6H), 1.75 (d, J = 8.5 Hz, 2H), 1.71 (d, J = 8.7 Hz, 2H), 1.53 (s, 6H), 1.22 (t, J = 6.4 Hz, 2H), 1.13 (s, 6H).

[0107] (4) Synthesis of formula ZF7:

[0108] Under argon protection, intermediate 4 (3.50 g, 5.46 mmol), bromotrimethylsilane (8.36 g, 54.6 mmol) and 5 mL 1,4-dioxane were added to a 100 mL two-necked bottle in sequence, and the mixture was reacted at room temperature for 18 h. The solvent was removed by vacuum distillation, and 5 mL methanol and 15 mL water were added to the obtained solid in sequence, and stirring was continued for 3 h. The reaction solution was filtered and washed with water to obtain a crude product. The crude product was then recrystallized from ethanol and water to obtain 2.71 g of white ZF7 product with a yield of 85%.

[0109] The structural characterization data of the synthesized ZF7 compound are: 1 H NMR (400MHz, DMSO): δ8.57(s,1H),8.16(s,2H),8.14(s,2H),7.88(d,J=7.4Hz,1H),7.83(s,1H),7.63(s,2H),7.61(s,2H),7. 47(s,1H),7.45(s,2H),7.43(s,1H),7.19(s,2H),4.40(s,2H),1.61(d,J=2.7Hz,2H),1.58(s,2H),1.54(s,6H),1.52(s,2H).

[0110] Example 5

[0111] The self-assembled monolayer hole transport material ZF1 prepared in Example 1 has a nuclear magnetic resonance spectrum as shown in Figure 1 As shown. At the same time, the thermogravimetric analysis of the molecule shows that the decomposition temperature of the molecule is 221°C, showing strong thermal stability ( Figure 5 shown).

[0112] This embodiment provides a formula ZF1 prepared in Example 1, and a perovskite solar cell is prepared according to the literature: M. Liu; L. Bi; W. Jiang; et al. Adv. Mater. 2023, 2304415. Test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), and data acquisition uses Keithley 2400 digital source meter. Test results are shown in Figure 6 The short-circuit photocurrent density of the battery device reached 25.61 mA cm -2 , the open circuit voltage is 1.163V, the fill factor (FF) is 0.8188, and the photoelectric conversion efficiency reaches 24.39%.

[0113] Example 6

[0114] The self-assembled monolayer hole transport material ZF2 prepared in Example 2 has a nuclear magnetic resonance spectrum as shown in Figure 2 As shown. Thermogravimetric analysis diagram ( Figure 6 ) showed that the decomposition temperature of the molecule was 315°C, and the introduction of surface fluorine atoms could further promote the improvement of the thermal stability of the molecule.

[0115] This embodiment provides a formula ZF2 prepared in Example 2, and a perovskite solar cell is prepared according to the literature: M. Liu; L. Bi; W. Jiang; et al. Adv. Mater. 2023, 2304415. Test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), and data acquisition uses Keithley 2400 digital source meter. Test results are shown in Figure 6 The short-circuit photocurrent density of the battery device reached 25.96 mA cm -2 , the open circuit voltage is 1.160V, the fill factor (FF) is 0.8001, and the photoelectric conversion efficiency reaches 24.1%.

[0116] Example 7

[0117] The self-assembled monolayer hole transport material ZF3 prepared in Example 3 has a nuclear magnetic resonance spectrum as shown in Figure 3 As shown. Thermogravimetric analysis diagram ( Figure 7 ) showed that the decomposition temperature of the molecule was 301°C, exhibiting excellent thermal stability.

[0118] This embodiment provides a formula ZF3 prepared in Example 3, and a perovskite solar cell is prepared according to the literature: M. Liu; L. Bi; W. Jiang; et al. Adv. Mater. 2023, 2304415. Test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), and data acquisition uses Keithley 2400 digital source meter. Test results are shown in Figure 6 The short-circuit photocurrent density of the battery device reached 25.96 mA cm -2 , the open circuit voltage is 1.18V, the fill factor (FF) is 0.7995, and the photoelectric conversion efficiency reaches 24.44%.

[0119] Example 8

[0120] The self-assembled monolayer hole transport material ZF7 prepared in Example 4 has a nuclear magnetic resonance spectrum as shown in Figure 4 As shown. Thermogravimetric analysis diagram ( Figure 8 ) showed that the decomposition temperature of the molecule was 218°C, showing excellent thermal stability.

[0121] This embodiment provides a formula ZF3 prepared in Example 3, and a perovskite solar cell is prepared according to the literature: M. Liu; L. Bi; W. Jiang; et al. Adv. Mater. 2023, 2304415. Test light source: AM 1.5 (solar simulator-Oriel 91160-1000, 300W), and data acquisition uses Keithley 2400 digital source meter. Test results are shown in Figure 6 The short-circuit photocurrent density of the battery device reached 24.63 mA cm -2 , the open circuit voltage is 1.13V, the fill factor (FF) is 0.8323, and the photoelectric conversion efficiency reaches 23.16%.

[0122] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-assembled monolayer organic semiconductor material based on indeno[2,1-b]carbazole, characterized in that: The chemical structure is shown below: The substituent R is bromo, p-methoxyphenyl, p-fluorophenyl, 3,4,5-trifluorophenyl, pentafluorophenyl, 3,5-di(trifluoromethyl)phenyl, dibenzopyrrolyl, 4,4-dimethyldibenzoacridinyl or 3,5-dicarboxylic acid methyl ester phenyl.

2. The method for preparing a self-assembled monolayer organic semiconductor material based on indeno[2,1-b]carbazole according to claim 1, characterized in that: The following steps are involved: S1: Compound 1 undergoes a coupling reaction with a boronic acid or boronic acid lipid containing an R group to generate an intermediate 2; S2: Substitution reaction of intermediate 2 with dibromoalkane to generate intermediate 3; S3: causing intermediate 3 to undergo a substitution reaction with triethyl phosphite to generate intermediate 4; S4: hydrolyzing the intermediate 4 to generate the target product, i.e., the self-assembled monolayer material; The substituent R is bromo, p-methoxyphenyl, p-fluorophenyl, 3,4,5-trifluorophenyl, pentafluorophenyl, 3,5-di(trifluoromethyl)phenyl, dibenzopyrrolyl, 4,4-dimethyldibenzoacridinyl or 3,5-dicarboxylic acid methyl ester phenyl.

3. The method for preparing a self-assembled monolayer organic semiconductor material based on indeno[2,1-b]carbazole according to claim 2, characterized in that: In S1, under argon protection conditions, in toluene solvent, compound 1 is reacted with boric acid or boric ester containing a substituent R under the action of tetrakistriphenylphosphine palladium and potassium carbonate to generate compound 2, wherein the amount of the compound used is calculated by the amount of substance, compound 1: boric acid or boric ester containing a substituent R: tetrakistriphenylphosphine palladium: potassium carbonate = 1: 1-2: 0.02-0.1: 4-10, the reaction temperature is 90-110° C., and the reaction time is 6-12 h.

4. The method for preparing a self-assembled monolayer organic semiconductor material based on indeno[2,1-b]carbazole according to claim 2, characterized in that: In the S2, compound 2 is dissolved in DMF, and under the action of potassium hydroxide and tetrabutylammonium bromide (TBAB), a substitution reaction occurs to generate compound 3, wherein the amount of the compound is calculated based on the amount of substance, compound 2: dibromobutane = 1:5-20, the reaction temperature is 60-70°C, and the reaction time is 4-8h.

5. The method for preparing a self-assembled monolayer organic semiconductor material based on indeno[2,1-b]carbazole according to claim 2, characterized in that: In S3, compound 3 is reacted with triethyl phosphite under an argon atmosphere to generate compound 4, wherein the molar ratio of compound 3 to triethyl phosphite is 1:5-40, the reaction temperature is 100-200° C., and the reaction time is 10-20 h.

6. The method for preparing a self-assembled monolayer organic semiconductor material based on indeno[2,1-b]carbazole according to claim 2, characterized in that: In S4, compound 4 and bromotrimethylsilane are mixed in 1,4-dioxane, and a hydrolysis reaction is carried out under an argon atmosphere. The reaction is carried out at 25 to 100° C. for 10 to 24 hours to obtain the target product ZF; the molar ratio of compound 4 to bromotrimethylsilane is 1:5 to 10.

7. Use of the self-assembled monolayer organic semiconductor material based on inden[2,1-b]carbazole as claimed in claim 1 in perovskite solar cells.

Citation Information

Cited By

  • Self-assembled monomolecular layer hole transport material of indeno-carbazole derivative and preparation method and application of self-assembled monomolecular layer hole transport material

    CN121378339A

  • Indenocarbazole-based bisphosphonic acid self-assembled monolayer material, synthesis method and application thereof

    CN122726210A